Framing the Frame: Embedded Narratives, Enabling Texts, and Frankenstein - O’Dea, Gregory (Romanticism on the Net, 2003)
AbstractReader-focused analyses of frame narrative (usually assuming and elaborating a liminal, distinguishing, or transitional “picture-frame” metaphor) are incomplete, describing only the initial experience of “coming at” and “moving off from” the text as a pre-existing artifact. An alternative analysis would emphasize narrative acts and enabling texts (guided by the metaphor of an internal, form-giving “frame-work”), and thus describe the process by which the textual artifact comes into being, shaping itself over time into the text we eventually read. In Mary Shelley's Frankenstein, we might distinguish three frame sequences: a reading sequence, an action sequence, and a narrative sequence. The narrative sequence is the primary, enabling frame shaping the novel, and is dependent upon three levels of narrative refiguring: rhetorical, elemental, and intentional. Each narrative act in Shelley’s novel is enabled and shaped by a previous narrative act, and each narrative text produced by these acts is the peculiar result of the narrative sequence that engenders it. The tension between narrative act and narrative text in Frankenstein forms a fundamental dialectic process, producing an ambiguously authoritative artifact.